2009
DOI: 10.1080/01411590902978502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on morphology and phase transformations of nano-crystalline silica obtained from rice husk

Abstract: Pyrolysis of rice husk (RH), an agricultural by-product, was studied at different temperatures (700-1100 C) in the presence of air. The changes in morphologies, compositions and phase transformations were studied critically by scanning electron microscopy, energy dispersive spectroscopy and X-ray diffractometry, respectively. Different phases of silica obtained from RH were observed with respect to change in temperatures. Crystallite size and the amount of silica obtained from RH at each temperature were worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…1) and the data obtained are tabulated in Table 1. A detailed discussion of chemical analysis was reported elsewhere [17]. The C/SiO 2 weight ratio of the rice husk material is higher than the required weight ratio for the formation of SiC from SiO 2 with C as shown in above equations (1) to (3).…”
Section: Resultsmentioning
confidence: 99%
“…1) and the data obtained are tabulated in Table 1. A detailed discussion of chemical analysis was reported elsewhere [17]. The C/SiO 2 weight ratio of the rice husk material is higher than the required weight ratio for the formation of SiC from SiO 2 with C as shown in above equations (1) to (3).…”
Section: Resultsmentioning
confidence: 99%
“…In an investigation on the effect of temperature on the morphology and phase transformations of nano-crystalline silica obtained from rice husk, Sarangi et al reported a graph of the variation of crystallite size of the calcined materials as a function of temperature [134].This profile shows two regimes: the first one, for temperatures between 500 and 700°C, corresponds to a situation where the crystallite size grows slowly with temperature. The second one, for temperatures higher than 700°C, the aggregation effects become very important producing a significant growth in the crystallile size.…”
Section: (Figure 13)mentioning
confidence: 96%
“…Hemicelluloses used as recourse of activated carbon, xylose and silicon dioxide. RH contents main elemental components as Carbon 37.05%, Hydrogen 8.80%, Nitrogen 11.06%, Silicon 9.01% and Oxygen 35.03 % (Joseph et al, 1999;Sarang et al, 2009). Husk contains 17-25% silica (Patel et al, 1987;Conradt et al, 1992;Real et al, 1996).…”
Section: Composition Of Rice Huskmentioning
confidence: 99%